Hidden family rules: perspective on a dysfunctional paternalistic system and the persistence of pain - Hudson, Matt; Johnson, Mark I. (Frontiers in Pain Research, 2023)
This article explores how paternalistic control and power reside within the family system and how this may influence pain and its persistence. Drawing upon clinical case studies and existing literature, this exploration emphasises the role of paternal dysfunction in creating emotional memory images and delves into how this may influence the chronification and treatment resistance of pain (i.e., making pain “sticky”). We argue that a dysfunctional paternalistic family system, often characterised by authoritarian dynamics, emotional neglect, and abuse, results in adverse experiences and emotional memory images that create a fertile ground for the entrenchment and propagation of psychosomatic symptoms, including pain. Further, the paper emphasizes the potential intergenerational effects of such a scenario, where inherited “Family Rules” drive maladaptive coping mechanisms, which contribute to the persistence of psychological and physiological distress across generations. Understanding these complexities offers new perspectives on treating psychological disorders and their physiological ramifications. It also highlights the urgency of addressing dysfunctional familial dynamics in psychotherapeutic interventions for both immediate and long-term psychophysiological health outcomes.